The degree of customer satisfaction in university restaurants: The case of the University of Évora in Portugal - Saraiva, Margarida (2011)
Organizations in globalized and consumer societies are offering progressively more quality products in order to satisfy their customers. University restaurants are not indifferent to this phenomenon and also care about the degree of customer satisfaction. The present study was planned and developed in order to address this issue. The purpose of this investigation was to measure the degree of customer satisfaction in the restaurant “Cozinha do Cardeal” of the University of Evora (Portugal), so as to improve services according to the needs and wishes of the regular users. In overall terms, it was found that the quality of service offered by this restaurant was satisfactory. However, further analysis showed that the most critical items were included in the variable “external environment”, namely: “accessibility for the disabled” and “parking”. Moreover, emerged as the most requested needs the following: “a more varied menu” and “an extension of opening hours”. Given these results, we recommend the restaurant management to implement urgent measures to improve services, which may contribute not only to reduce the dissatisfaction of the regular customers but also to attract new ones.